Hybrid Contract in Islamic Financial Services - Hasanudin Hasanudin; Nisrina Mutiara Dewi; Gine Putri Pertiwi; Feby Wijayanti (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
The hybrid contract is needed to accommodate modern transactions unavailable in the classical Islamic period. The current financial service products use hybrid contracts, such as in debt transfer, import and export letters of credit, and credit cards. The evaluation of the use of contracts in these products reveals the use of multiple alternative contracts in debt transfer and Letters of Credit; and single contract alternative for credit card services. This study shows the complexity of contracts in modern financial products, requiring more complex documentation. The merger of several contracts in one transaction is based on the argument that there is no prohibition on using multiple contracts in one transaction, as long as it avoids usury (ribā). AbstrakPenggabungan akad merupakan kebutuhan untuk mewadahi transaksi modern yang tidak ditemukan di masa Islam klasik. Bentuk penggabungan akad tersebut terjadi di antaranya pada produk jasa keuangan modern seperti pengalihan utang, Letter of Credit impor dan ekspor, dan kartu kredit. Dengan mengevaluasi penggunaan akad-akad dalam produk tersebut ditemukan beberapa alternatif penggabungan akad pada produk pengalihan hutang dan Letter of Credit, serta satu alternatif penggabungan akad untuk produk kartu kredit. Penggabungan akad tersebut didasarkan atas argumen tidak ada larangan penggabungan akad selama tidak menimbulkan ribā. Hasil penelitian ini menunjukkan kompleksitas akad pada produk keuangan modern yang pada praktiknya membutuhkan dokumentasi yang lebih kompleks.